Remembering the Founder, the Mentor and an Invisible Guide Forever - Rodriguez, Humberto Gonzalez (International Journal of Bio-resource and Stress Management, 2020)
It is the remembrance of Prof. (Dr.) Ratikanta Maiti, a world-renowned botanist and crop physiologist on his birthday 24th April, 1935. He worked on jute and allied fibers at the former Jute Agricultural Research Institute of the Indian Council of Agricultural Research for nine years, and on sorghum and pearl millet at the International Crops Research Institute for the Semi-Arid Tropics for 10 years. After that he worked for more than 25 years as a professor and research scientist at three different universities in Mexico. He also served as a Research Advisor at Vibha Seeds, Hyderabad, India, and as a Visiting Research Scientist in the School of Forest Science, Autonomous University of Nuevo Leon, Mexico. As an author of more than 50 books and about 500 research papers, he was conferred with several international awards including the Ethno-Botanist Award (USA) sponsored by Friends University, Wichita, Kansas, the United Nations Development Program; the senior research scientist award by Consejo Nacional de Ciencia y Tecnología (CONACYT, in Spanish), Mexico; and a gold medal for India in 2008 offered by the American Biographical Institute (ABI). He is the Chairman of the Ratikanta Maiti Foundation. He was the pioneer as chief editors of three international journals including the International Journal of Bio-resource and Stress Management (IJBSM). Dr. Maiti passed away on 19 June 2019.